Composition of place, minority vs. majority group-status, & contextualized experience: The role of level of group representation, perceiving place in group-based terms, and sense of belonging in shaping collective behavior. - Demis E Glasford (PLoS ONE, 2021)
The current studies (N = 1,709) explore why demographic composition of place matters. First, this work demonstrates that relative level of group representation affects one's experience of place in the form of self-definition (self-categorization), perceptions of place being representative or characteristic of factors that distinguish the group from others (place-prototypicality), and sense of belonging (place-identification; Studies 1a-1e; Studies 2a & 2b). Second, the studies illustrate that group representation within place shapes the way group member's approach (i.e., expectations of group-based treatment and procedural justice; Studies 2a-2c), understand (i.e., attribution for group-based events, Study 2b; responsiveness to bias-reduction intervention, Study 4a; sense of solidarity, Study 4b), and behave (i.e., prejudice, Studies 3a & 3b; collective action, Study 4c). More broadly, I present a Social identity Paradigm for Contextualized Experience (SPACE) that provides an organizing framework for the study of the impact of characteristics of place on social identity-based contextualized experience and (in turn) collective behavior. Taken together, the findings provide evidence of distinct psychological experience and orientation as a function of minority versus majority-group status within place, as well as for a group-based approach to place. Implications for the study of collective and intergroup behavior are discussed.